Public relations communication behavior through a local-wisdom approach: the findings of public relations components via ethnography as methodology - Hidayat, Dasrun; Kuswarno, Engkus; Zubair, Feliza; Hafiar, Hanny (Penerbit Universiti Kebangsaan Malaysia, 2018)
There is a correlation between the concept of public relations with the cultural activities of Jakhu Suku. The relationship is built through the behavior of Jakhu Suku communications in the tradition of giving a title that always emphasises the planning and evaluation stage. This is what lies behind this study with a locus of cultural research with a public relations theory approach. To answer the purpose of research, interviews and observation were used by involving all customary devices in the Village Banjar Negeri Lampung Province Indonesia. The study found that the behavior of Jakhu Suku communications in carrying out cultural activities begins with pekhsiapan (preparation), khencana (planning), lestakhi (execution), penghengok (support) and penghanggum (trust). All the Jakhu Suku cultural concepts are relevant to the communication planning components including Insight, Strategic Programs, Implementation Programs, Action, and Reputation (the IPPAR model). The Jakhu Suku culture can be referred to as a component of cultural-based public relations communication behavior. This component can be applied in the context of corporate, government and non-government public relations. Public relations companies and governments are profit-oriented, while non-government-based nonprofits such as culture are found in community groups or communities. The communication behavior component of the IPPAR model can be classified as a component of ethnography public relations. The methodology focuses on culture-based public relations communication behavior.